2014
DOI: 10.1007/s10120-014-0388-5
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of gastric cancer treatment in patients with positive peritoneal cytology

Abstract: Gastric cancer patients with positive peritoneal cytology as the only marker of metastatic disease have poor prognoses. There is no universal consensus on the most appropriate treatment regimen for this particular patient group. We reviewed and analyzed published data to determine the optimal treatment regimen for patients with peritoneal cytology-positive gastric adenocarcinomas. Six electronic databases were explored [PubMed, Cochrane (Systematic Reviews and Controlled Trials), PROSPERO, DARE, and EMBASE]. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 41 publications
(65 reference statements)
0
24
0
Order By: Relevance
“…The oral anticancer drug S1 is a fluoropyrimidine derivative, combining tegafur with two modulators. A recent meta-analysis showed that the use of S1 monotherapy was associated with a significant survival benefit (HR = 0.48, 95%CI: 0.32-0.70, P = 0.0002)[41]. The advantage of S1 over other chemotherapeutic agents is its ability to attain higher concentrations intraperitoneally, due to the higher concentrations of 5-FU and CDHP achieved in peritoneal tumors than in plasma[42,43].…”
Section: Optional Agents For Intraperitoneal Treatmentmentioning
confidence: 99%
“…The oral anticancer drug S1 is a fluoropyrimidine derivative, combining tegafur with two modulators. A recent meta-analysis showed that the use of S1 monotherapy was associated with a significant survival benefit (HR = 0.48, 95%CI: 0.32-0.70, P = 0.0002)[41]. The advantage of S1 over other chemotherapeutic agents is its ability to attain higher concentrations intraperitoneally, due to the higher concentrations of 5-FU and CDHP achieved in peritoneal tumors than in plasma[42,43].…”
Section: Optional Agents For Intraperitoneal Treatmentmentioning
confidence: 99%
“…In the gastric, colon and gynecological malignancies, microscopic occult peritoneal metastases preceded the emergence of macroscopic metastases and such patients were precluded from radical surgery [8, 2830]. However, the impact of CY+ on long-term survival of pancreatic cancer was uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of cytology‐positive gastric cancers, we showed that absence of peritoneal dissemination can predict long‐term survival of patients with advanced gastric cancer with a positive cytology test and long‐term postoperative adjuvant therapy with S‐1 was required for survival of patients with CY1 in the absence of peritoneal dissemination over 5 years . A recent systematic review also showed that the use of S‐1 monotherapy was associated with a significant survival benefit in CY1 patients (HR 0.48; 95% CI 0.32‐0.70; P = 0.0002) . Although randomized controlled trials are needed, S‐1 monotherapy, due to its easy feasibility, may be very promising for gastric cancer with the unresectable factor of cytology positive alone, and this theoretical rationale is applicable to Type III/IV gastric cancer.…”
Section: Therapeutic Strategies According To Macroscopic Classificatimentioning
confidence: 90%